In their own words: criminals on crime: an anthology - Birzer, Michael L. (Oxford University Press, 2017)
Doing fieldwork with offenders -- Researching crack dealers : dilemmas and contradictions / Bruce Jacobs -- Consenting to talk : why inmates participate in prison research / Heith Copes and Andy Hochstetler -- Criminal lifestyles and decision making -- Deciding to commit a burglary / Richard T. Wright and Scott H. Decker -- Opportunities and decisions : interactional dynamics in robbery and burglary groups / Andy Hochstetler -- Auto theft and restrictive deterrence / Bruce Jacobs and Michael Cherbonneau -- Property crime -- Establishing connections : gender, motor vehicle theft, and disposal networks / Christopher W. Mullins and Michael C. Cherbonneau -- The devil made me do it : use of neutralizations by shoplifters / Paul Cromwell and Quint Thurman -- Identity theft : assessing offenders' motivations and strategies / Heath Copes and Lynne Vieraitis -- Violent crime -- Gendering violence : masculinity and power in men's accounts of domestic violence / Kristin L. Anderson and Debra Umberson -- Serendipity in robbery target selection / Bruce Jacobs -- Peaceful warriors : codes for violence among adult male bar fighters / Heith Copes, Andy Hochstetler, and Craig J. Forsyth -- Occupational and white-collar crime -- Crime on the line : telemarketing and the changing nature professional crime / Neal Shover, Glenn S. Coffey, and Dick Hobbs -- Drugged druggists : the convergence of two criminal career trajectories / Dean A. Dabney and Richard C. Hollinger -- Illegal occupations -- The "myth of organization" of international drug smugglers / Scott Decker and Jana S. Benson -- Informal control and illicit drug trade / Scott Jacques and Richard Wright -- A "perversion" of choice sex work offers just enough in chicago's urban ghetto / Eva Rosen and Sudhir Alladi Venkatesh -- Gangs and crime -- Gang-related gun violence : socialization, identity, and self / Paul B. Stretesky and Mark R. Pogrebin -- Gender and victimization risk among young women in gangs / Jody Miller -- Voices from the barrio : chicano/a gangs, families, and communities / Marjorie S. Zatz and Edwardo L. Portillos -- Drugs and crime -- "E" is for ecstasy : a participant observation study of ecstasy use / Wilson R. Palacios and Melissa E. Fenwick -- "Cooks are like gods" : hierarchies in methamphetamine-producing groups / Robert Jenkot -- Quitting crime -- Getting out of the life : crime desistance by female street offenders / Ira Sommers, Deborah R. Baskin, and Jeffery Fagan -- The authors examine the process by which women offenders desist from crime -- The victimization : termination link / Scott Jacques and Richard Wright